2020
DOI: 10.1093/ehjqcco/qcaa059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the diagnostic and prognostic value of biomarkers for heart disease and major adverse cardiac events in patients with muscular dystrophy

Abstract: Aims Heart disease is recognized as the leading cause of morbidity and mortality in patients with muscular dystrophy (MD). Our study demonstrates the clinical utility of cardiac biomarkers to improve the diagnosis of cardiomyopathy and prognostication of major adverse cardiac events (MACE) in these vulnerable patients. Methods and Results We prospectively followed 117 patients (median age, 42 (interquartile range [IQR], 26-50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…When stroke was analyzed as a separate endpoint, a trend in older patients suffering from stroke (40 [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] vs. 25 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] years; P = 0.08) was observed. Those patients more frequently had atrial standstill (AS) (50% vs. 5%; P = 0.02) and atrio-ventricular (AV) block (83% vs. 15%; P = 0.002) at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…When stroke was analyzed as a separate endpoint, a trend in older patients suffering from stroke (40 [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] vs. 25 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] years; P = 0.08) was observed. Those patients more frequently had atrial standstill (AS) (50% vs. 5%; P = 0.02) and atrio-ventricular (AV) block (83% vs. 15%; P = 0.002) at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Heart disease is highly prevalent in patients with MD and is a major determinant of their clinical outcomes. (Nikhanj et al, 2020 ; Nikhanj, Yogasundaram, et al, 2020 ) 12‐lead electrocardiogram assessment is easily accessible, requires minimal training, and is of negligible burden on healthcare resources, making it a convenient and feasible method of assessing heart disease. Our investigation evaluated the use of conventional ECG‐LVH criteria in patients with MD.…”
Section: Discussionmentioning
confidence: 99%
“…Although we were not able to capture the association between cardiac biomarkers and anatomical LVH in this cohort due the low prevalence, we support the proposed prognostic value of comparable B‐type natriuretic peptide and hsTnI for MACE in these patients, independent of LVH. (Nikhanj, Nichols, et al, 2020 ) We acknowledge that ECG‐LVH could be representative of interstitial and ion channel remodeling in the absence of myocyte hypertrophy. (Aro Aapo & Chugh, 2016 ) With regard to the indication of LA enlargement by ECG, previous studies have shown that the level of specificity could prove useful for confirmation of indications by imaging but not for diagnosis, similar to our findings with ECG‐LVH.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 117 patients with DMD, Becker muscular dystrophy (BMD), DMD/BMD carrier, limb-girdle muscular dystrophy (LGMD), facioscapulohumeral dystrophy (FSHD) and myotonic dystrophy (DM) type I found a threefold increased risk of cardiac disease in subjects with an hs-cTnI level greater than 7.6 ng/L (Access High Sensitivity Troponin I Assay, Beckman-Coulter; normal <2.3 ng/L). 15 In a study of 53 subjects with dystrophic myopathies (including DMD, DMD carrier, BMD, LGMD 2A, FSHD), DM types I and II, and Becker/Thomsen myotonias, only three subjects, two with DMD and one with DM, had elevated cTnI levels and all three had evidence of cardiac disease. 13 Other studies have also demonstrated increases in cTnI levels in DMD and BMD.…”
Section: Troponin and Neuromuscular Diseasesmentioning
confidence: 99%